Efeito priming em função da qualidade dos resíduos culturais, temperatura e preparo da amostra de solo sob plantio direto - Zuza, José Flavio Cardoso (2023)
The occurrence and intensity of the priming effect (PE) can influence the amount of organic carbon (C) stored in the soil. Understanding how the quality of plant residues, temperature and sample preparation impact PE in no-tillage is important for understanding the effect of soil and crop management and climate change on C fluxes in the soil. In article I, the objective was to understand the effect of waste quality and temperature on the transformations of C in the soil and the intensity of EP. For this, an incubation study was developed with a sandy dystrophic Red Argisol collected from the 0-5 cm layer under PD. The experiment was conducted for 60 days in a completely randomized design with four replications. The treatments consisted of the use of two plant residues enriched with 13C (wheat and vetch) and two temperatures (15 and 25°C) and a control treatment. In article II, the objective was to evaluate the impact of physical disturbance caused by soil sample preparation (sieving <4mm) on the direction and intensity of EP in different soils under PD. The soils, two sandy and two clayey, were collected in areas under a long-term direct planting system. The evaluated treatments were composed of undisturbed (IND) and deformed (DEF) samples (<4 mm) of the four soils, with and without wheat leaves enriched with 13C. C mineralization was evaluated by quantifying CO2 released during 120 days of incubation. The results of article I indicate that the addition of plant residues to the soil causes positive EP, but in the short term the EP is not affected by the temperature and quality of the residues. Under these conditions, legume residues have greater potential to promote a positive C balance in the soil, as these residues promote a greater amount of new C in the soil than wheat residues, especially at higher temperatures. The results of paper II indicate that the use of DEF soil samples has a reduced effect on C mineralization of soil organic matter (SOM) and wheat leaves. However, it has a significant effect on the direction and intensity of EP. On average across the four soils, the EP was 26% higher with the DEF sample than with the IND sample (149 vs 38 mg C-CO2 kg-1 soil). Although no interaction was found between soils and sample preparation, the results indicate that sandy soils are more sensitive to sample preparation than clayey soils. The results of the present study in which sieving the soil sample (<4mm) increases the EP intensity indicate that the use of deformed soil samples under PD leads to an overestimation of the effect of plant residues on the EP under PD.